Assessment and Creativity Stimulus in School Context. (16th January 2015) - Cardoso, Ana Paula; Malheiro, Rogério; Rodrigues, Paula; Felizardo, Sara; Lopes, Ana
Abstract: Creativity is a fundamental aptitude today, with teachers playing an important role in its promotion. So, this study intends to examine to what extent teachers of Visual and Technological Education (EVT) evaluate, objectively, the creative level of their students and which strategies they put into practice, in order to stimulate student creativity. A comparative research of a descriptive-correlational nature was undertaken, comprising a questionnaire to twenty nine 2nd Cycle of Basic Education teachers from the Viseu municipality state schools (Portugal) and the application of the Torrance Test of Creative Thinking to 46 students from two classes at one of the schools. The data reveal that there are no statistically significant differences between the assessment of student creativity obtained by the Torrance Test and the creative level assigned by teachers. We can also verify, with relation to stimulating creativity, that teachers of Visual and Technological Education opt, more frequently, for psychological stimuli and, less frequently, for educational strategies that involve carrying out assignments/research. Educational implications are addressed.